2020
DOI: 10.1186/s12864-020-06822-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of host-encoded circular RNAs highlights their potential role during the Japanese encephalitis virus-induced neuroinflammatory response

Abstract: Background: Japanese encephalitis virus (JEV) is one of the common causes of acute encephalitis in humans. Japanese encephalitis is characterized by the uncontrolled release of inflammatory cytokines, which ultimately results in neuronal cell damage. In recent years, with the advancement of high-throughput sequencing technology, studies have shown that circRNAs, by competing with endogenous miRNAs, play a vital role in the pathology of CNS diseases. However, it is unknown whether circRNAs participate in JEV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…In Japanese encephalitis, characterized by the uncontrolled release of inflammatory cytokines in the brain, HTS identified 180 DE circRNAs in JEV-infected murine brains. Gene ontology and KEGG enrichment analyses revealed that the circRNA parental genes were related to neurotransmission, histone modifications, transcription misregulation, and inflammation-associated calcium signaling 99 . Additional analysis of one of the DE circRNAs, circ-0000220, revealed that either knockdown of this circRNA or overexpression of its target miR-326-3p in BV-2 microglia cells lowered the production of inflammatory cytokines 99 .…”
Section: Circrnas In Pd Pathogenetic Processesmentioning
confidence: 99%
“…In Japanese encephalitis, characterized by the uncontrolled release of inflammatory cytokines in the brain, HTS identified 180 DE circRNAs in JEV-infected murine brains. Gene ontology and KEGG enrichment analyses revealed that the circRNA parental genes were related to neurotransmission, histone modifications, transcription misregulation, and inflammation-associated calcium signaling 99 . Additional analysis of one of the DE circRNAs, circ-0000220, revealed that either knockdown of this circRNA or overexpression of its target miR-326-3p in BV-2 microglia cells lowered the production of inflammatory cytokines 99 .…”
Section: Circrnas In Pd Pathogenetic Processesmentioning
confidence: 99%
“…RNA sequence analyses of JEV-infected mice brain tissues have also unveiled widespread alterations in the expression of other non-coding RNAs that include long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs). Functional enrichment analysis of differentially expressed lncRNAs and circRNAs exhibit a strong relationship with cellular processes related to innate immunity, inflammation, neurotransmission, and transcription dysregulation [ 42 , 43 ]. The siRNA-mediated silencing of lncRNAs E52329 and N54010 caused dephosphorylation of JNK and MKK4 proteins in cultured mouse microglia infected with JEV, resulting in the deactivation of JNK/MKK4 pathway and reduced inflammatory cytokines release [ 42 ].…”
Section: Activation Of Glial and Neuronal Cellsmentioning
confidence: 99%
“…The siRNA-mediated silencing of lncRNAs E52329 and N54010 caused dephosphorylation of JNK and MKK4 proteins in cultured mouse microglia infected with JEV, resulting in the deactivation of JNK/MKK4 pathway and reduced inflammatory cytokines release [ 42 ]. Since circRNAs regulate mRNA expression via sponging miRNAs, the overexpression or knockdown of one of JEV-triggered circRNAs, circRNA-0000220, ameliorated inflammatory response in mouse microglial cells, which might have regulated through sponging the miR-326-3p and subsequently modulating the stability of miR-326-3p-target mRNAs, viz ., MK2, Bcl-3, and TRIM25 [ 43 ]. Further studies providing deeper mechanistic insights into the functions of lncRNAs or circRNAs in mediating the neuroinflammatory response during JEV infection are required which may highlight potential therapeutic targets to treat JE.…”
Section: Activation Of Glial and Neuronal Cellsmentioning
confidence: 99%
“…The 3′ and 5′ ends of circRNA are connected to form a unique and complete circular covalent closed structure, which are resistant to RNA exonuclease and possess higher biological stability than that of linear RNA [ 8 , 10 ]. With the development of high-throughput sequencing technology, increasing numbers of circRNAs have been discovered and their biological characteristics and regulatory functions have been revealed [ 9 , 11 ]. Specific circRNAs can be used as miRNA sponges to regulate the transcription and post-transcription of miRNA-targeted genes, which play the role in several physiological and pathological processes, including proliferation, migration, and invasion [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Termed as “microRNA sponges,” these competitive inhibitors are transcripts that are expressed from strong promoters and contain multiple, tandem- binding sites to a microRNA of interest [ 13 ]. circRNAs have close clinical relevance to human diseases such as tumors, diabetes, and cardiovascular diseases [ 11 , 14 16 ]. For example, hsa_circ_0008285 has been reported to inhibit colorectal cancer cell proliferation and metastasis through sponging with miR-382-5p, promote the cervical cancer progression through sponging with miR-211-5p, and promote breast cancer progress through sponging with miR-1275 [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%